2022
DOI: 10.1094/phyto-08-21-0341-r
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Tomato Plants withTomato yellow leaf curl virusandTomato chlorosis virusAffects the Interaction with Host and Whiteflies

Abstract: Susceptible plants infected by single or multiple viruses can differ in symptoms and other alterations influencing virus dissemination. Furthermore, behavior of viruliferous vectors may be altered in certain cases to favor acquisition and inoculation processes conductive to virus transmission. We explored single and mixed infections frequently occurring in tomato crops, caused by two viruses transmitted by the whitefly Bemisia tabaci: Tomato yellow leaf curl virus (TYLCV, Begomovirus, Geminiviridae) and Tomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…In mixed infections, many begomoviruses co-existing in natural host plants have shown neutral synergistic interactions [ 50 , 51 , 52 ], which may lead to more severe disease complexes. The finding that tomato and muskmelon plants harbor a mixed infection of CLCuGeV and its associated DNA-satellites together with TYLCV or ToLCPalV might suggest that these viruses may complement each other, as is the case of previous reports on TYLCV [ 50 , 53 , 54 ]. Nevertheless, the association of OLCuOMB and OYCrCMA might be a host-switching strategy because CLCuGeV is mostly associated with CLCuGeB and/or CLCuGeA [ 19 , 34 , 55 ].…”
Section: Discussionmentioning
confidence: 76%
“…In mixed infections, many begomoviruses co-existing in natural host plants have shown neutral synergistic interactions [ 50 , 51 , 52 ], which may lead to more severe disease complexes. The finding that tomato and muskmelon plants harbor a mixed infection of CLCuGeV and its associated DNA-satellites together with TYLCV or ToLCPalV might suggest that these viruses may complement each other, as is the case of previous reports on TYLCV [ 50 , 53 , 54 ]. Nevertheless, the association of OLCuOMB and OYCrCMA might be a host-switching strategy because CLCuGeV is mostly associated with CLCuGeB and/or CLCuGeA [ 19 , 34 , 55 ].…”
Section: Discussionmentioning
confidence: 76%
“…After 3 weeks, viral accumulation was checked in systemic leaves by qPCR, and plants with similar viral accumulation levels were selected. Whitefly choice assays were performed as described by Ontiveros et al, 2022. Briefly, four different leaflets coming from TYLCV WTor mutant-infected tomato plants (2x each) were distributed in a plastic cage (25x25 cm), disposed around a central release platform where one whitefly was placed, and only the first choice within a time frame of 15 min was recorded. For each experiment, a total of 60 adults of Bemisia tabaci Mediterranean biotype were used (with each whitefly constituting an individual biological replicate).…”
Section: Whitefly Dual-choice Assaysmentioning
confidence: 99%
“…Since the CCL-like motif in C4 is broadly conserved and determines symptom development, but does not seem to play a significant role in viral performance in the plant, we wondered whether it may contribute to viral transmission by the insect vector, an essential part of the viral cycle in nature. TYLCV is exclusively transmitted by the whitefly Bemisia tabaci (Navot et al ., 1991), which was recently shown to be preferentially attracted to TYLCV-infected compared to uninfected tomato plants based on the perception of visual cues (Ontiveros et al ., 2022). In agreement with these results, choice assays (Figure S18) demonstrated that B. tabaci displays a preference for tomato plants infected with TYLCV (symptomatic) versus those infected with TYLCV C4 CCLm3 (asymptomatic), even when viral load is comparable (Figure 4e; Figure S18).…”
Section: Main Textmentioning
confidence: 99%
“…Studies of the co-infection of plant viruses in wild and domesticated plants are important for understanding plant virus epidemiology, evolution, and virus–virus interactions; consequently, these investigations will contribute to developing efficient and durable control strategies [ 1 , 2 , 3 , 4 , 5 ]. Co-infections by two or more plant viruses [ 6 , 7 , 8 , 9 , 10 , 11 ], different isolates of the same viruses [ 12 , 13 ], and the presence of quasispecies of the same viruses [ 12 , 14 , 15 , 16 , 17 ] in wild and domesticated plants seem likely to be common in nature [ 18 , 19 , 20 ]. Plants of the genus Narcissus in the family Amaryllidaceae are known as wild or domesticated plants, although it is difficult to draw a boundary distinguishing between these plants in Japan.…”
Section: Introductionmentioning
confidence: 99%